Preadministration of Fermented Sorghum Diet Provides Protection against Hyperglycemia-Induced Oxidative Stress and Suppressed Glucose Utilization in Alloxan-Induced Diabetic Rats - Olawole, Tolulope Dorcas; Okundigie, Margaret Imuetiyan; Rotimi, Solomon Oladapo; Okwumabua, Ogi; Afolabi, Israel Sunmola (Frontiers in Nutrition, 2018)
Sorghum bicolor grains are rich in phytochemicals known to considerably impact human health. Several health promoting products such as flour, staple food and beverages have been produced from sorghum grains. This study investigated the protective and modulatory effects of a sorghum diet on the genes of some antioxidant and glycolytic enzymes in alloxan-induced diabetic rats. The rats were randomly distributed into 6 groups, the control group received normal diet while the other groups were pre-treated with 12.5, 25, 50, 75 and 100 % of the sorghum diets daily for 8 weeks before the administration of a dose of alloxan (100 mg/kg BW), after which blood was collected and the liver was excised. The effects of the diets on blood glucose levels, liver dysfunction indices and markers of oxidative stress were assessed spectrophotometrically while the gene expression of key glycolytic enzymes and enzymatic antioxidants were assayed using reverse transcriptase polymerase chain reaction. It was observed that the pre-treatment of the experimental animals with the diets normalized the blood glucose before and after the administration of alloxan. The sorghum-treated groups also showed statistically significant (p < 0.05) decrease in liver dysfunction indices and markers of oxidative damage compared with the control. In addition, statistically the diets significantly decreased (p < 0.05) the relative expression of superoxide dismutase, glutathione peroxidase, glucokinase, phosphofructo-kinase and hexokinase genes in the experimental animals compared with the control. Overall, this study showed that the pre-administration of fermented sorghum diet significantly protected against hyperglycemia and suppressed glucose utilization via glycolysis in the liver of alloxan-induced diabetic rats. Thus, the consumption of sorghum diet may protect against hyperglycemia, oxidative damage and may therefore serve as functional food for management of diabetic mellitus.